The proposal of CDMA cell design scheme considering change in traffic distributions - Takeo, K.; Sato, S. (1998 IEEE 5th International Symposium on Spread Spectrum Techniques and Applications : proceedings, September 2-4, 1998, Sun City, South Africa : technical program, proceedings, 1998)
Non-uniform traffic could cause the disparity in communications quality among base stations (BSs) and lower system efficiency in CDMA systems. We have proposed a cell design algorithm to minimize the difference in communications quality between BSs at system introduction. The algorithm designs cell areas according to predicted traffic distribution with non-uniformity. In this paper, the proposed cell design algorithm is applied to an operating system in order to cope with change in traffic situations. The algorithm operates using measured SIR and reduces the difference in SIR between BSs.